Термонапряженное состояние цилиндрической теплозащитной оболочки при изменении угла намотки углеродного наполнителя - Грачева, Л.И. (Прикладная механика, 2014)
An effect of thermal deformation on the strength of a model of construction of heat-resistant coating is studied for temperatures exceeding 1000° C. This coating is the shell-type and made of carbon-carbon composite with the varying angle of winding to the shell axis. The physical-mechanical characteristics of composite are determined experimentally on the equipment available at the Institute for Problems of Strength with allowance for the conditions which model the real ones. A problem on the stress-strain state of the heat-resistant shell under heating is solved within the framework of the spatial theory of elasticity for the cylinder of length 340 mm, mean surface radius 90 mm, and thickness 10 mm. The findings allow to determine the stress state of coating in dependence on the type and orientation of carbon filler within the temperature range from 20° C to 1200° C. Досліджено вплив теплового деформування на міцність моделей конструкцій теплозахисних покриттів оболонкового типу вуглець-вуглецевих композиційних матеріалів (ВВКМ) при зміні кута намотки до осі циліндра при температурах, що перевищують 1000ºС. Фізико-механічні характеристики ВВКМ встановлено експериментально з врахуванням умов, що моделюють реальні, на установках Інституту проблем міцності НАНУ. Задачу про напружено-деформований стан теплозахисної оболонки при нагріванні розв’язано в рамках просторової теорії пружності для циліндра із ВВКМ довжиною 340 мм, радіусом середньої поверхні 90 мм, товщиною 10 мм. Отримані дані дають можливість визначити напружений стан елементів теплозахисного покриття оболонкового типу, що виготовлено намоткою, в залежності від технологічних факторів: типу і орієнтації вуглецевого наповнювача в інтервалі температур 20 … 1200ºС.